Decreased urinary excretion of the ectodomain form of megalin (A-megalin) in children with OCRL gene mutations - Suruda, Chikushi; Tsuji, Shoji; Yamanouchi, Sohsaku; Kimata, Takahisa; Huan, Nguyen Thanh; Kurosawa, Hiroyuki; Hirayama, Yoshiaki; Tsukaguchi, Hiroyasu; Saito, Akihiko; Kaneko, Kazunari (Pediatric nephrology (Berlin, West), 2017)
Background The oculocerebrorenal syndrome of Lowe gene ( OCRL ) is located on chromosome Xq25-26 and encodes an inositol polyphosphate-5-phosphatase (OCRL-1). Mutations in this gene cause Lowe syndrome (LS) or type 2 Dent disease, of which low-molecular-weight (LMW) proteinuria is a characteristic feature. Megalin is considered to play an important role in the development of renal tubular proteinuria. Two forms of megalin are excreted into the urine: full-length megalin (C-megalin) and megalin ectodomain (A-megalin). We have explored the role of megalin in the development of LMW proteinuria in patients with OCRL mutations by determining urinary megalin fractions. Methods We measured A- and C-megalin in spot urine samples from five male patients with OCRL mutations (median age 9 years), using sandwich enzyme-linked immunosorbent assays, and adjusted the obtained values for excreted creatinine. The results were compared with those of 50 control subjects and one patient with type 1 Dent disease (T1D). Results All patients demonstrated normal levels of urinary C-megalin. However, patients with OCRL mutations or T1D showed abnormally low levels of urinary A-megalin, with the exception of one 5-year-old boy with LS, who was the youngest patient enrolled in the study. Conclusions Decreased excretion of urinary A-megalin in four out of five patients with OCRL mutations suggests that LMW proteinuria may be caused by impaired megalin recycling within the proximal tubular cells. Homologous enzymes, similar to inositol polyphosphate-5-phosphatase B in mice, may help to compensate for defective OCRL-1 function during early childhood.